Goppa codes through polynomials of B[X;(1/2^2)Z_0] and its decoding principle - Andrade, Antonio Aparecido de [UNESP]; Shah, Tariq (Institute of Advanced Scientific Research, 2011)
In this paper, we present a decoding principle for Goppa codes constructed by generalized polynomials, which is based on modified Berlekamp-Massey algorithm. This algorithm corrects all errors up to the Hamming weight $t\leq 2r$, i.e., whose minimum Hamming distance is $2^{2}r+1$.
Keywords: Semigroup rings; Goppa codes; Modified Berlekamp-Massey algorithm